Answer:
Explanation:
To solve this, we need to remember that when you multiplicate two roots you can multiply the numbers inside the two roots and put them inside just one root.
So in this case we have ∛5ab² ·∛25ab
We are going to multiply the numbers inside the roots and we get
∛5ab²·25ab = ∛75a²b³
But 75 = 5³ so we have
∛75a²b³ = ∛5³a²b³
Since we have powers of 3 inside the root, we can take them outside the root with the exponent divided by 3.
∛5³a²b³ = 5b∛a²
Thus, the correct answer is a) 5b∛a²